Gestão territorial e ambiental de terras indígenas: implantação da PNGATI e do Projeto Gati na TI Xambioá - Lima, Eugislane Moreira (Universidade Federal do Tocantins, 2017)
The Constitution of the Federative Republic of Brazil (CFRB/1988) guarantees rights to indigenous people, among them the right to own lands. From this context, the state has created mechanisms for the recognition and demarcation of indigenous territories. However, the indigenous lands (IL) demarcated by the state, have today a status of conservation and preservation of the environment, with national and international recognition in environmental agendas, the target of various programs and projects aimed at environmental preservation. It is in this scenario that arise the first initiatives of the Project for the Environmental and Territorial Management of the Indigenous Lands (ETMIL). However, given the need for maintenance and conservation of indigenous lands, the state has created the National Policy for Environmental and Territorial Management of Indigenous Lands (NPETMIL) that is organized in guidelines and objectives for territorial management of the ILs. The policy is in force, having as one of its main implementation instruments, the ETMIL project. The project was developed as a pilot at the national level in 32 ILs that have become Reference Area (RA). In Tocantins state the project is developed in two ILs, which were, IL Xerente and IL Xambioá. This dissertation aimed to know how was the development of the ETML project and consequently the NPETMIL in IL Xambioá, in perspective of Karajá Xambioá people.